Food babe family : more than 100 recipes and foolproof strategies to help your kids fall in love with real food - Hari, Vani (Hay House, Inc., 2023)
"The multimillion dollar food industry has used their vast resources to target parents, convincing them that it's hard work to feed their children good food. But there's another way, and with this book, food activist and best-selling author Vani Hari provides you with all the tools, information, and recipes you need to feed your children in a way that will foster a love for real food and set them up for a life of healthy eating. In Food Babe Family, Vani dispels popular myths about feeding our kids; offers more than 100 delicious recipes that make it simple to put healthy, real food on the table; and helps parents start children on a lifelong path of making good food choices"--